2004
DOI: 10.1051/0004-6361:20035603
|View full text |Cite
|
Sign up to set email alerts
|

Size estimates of some optically bright KBOs

Abstract: Abstract. Seven recently detected optically "bright" Kuiper-Belt-Objects (KBOs) were observed at 250 GHz using the Max-Planck Millimeter Bolometer (MAMBO) array at the IRAM 30 m telescope. Only the optical binary KBO (47 171) 1999 TC36 was detected, whose components differ optically by ∆m ≈ 2 mag. Assuming that the derived mean geometric albedo of p = 0.05 is identical for both, the component diameters become 566 and 225 km. For the other six objects upper limits to their sizes and lower limits for their albed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…near a density of 1000 kg m −3 , the albedo is greater than 0.1, significantly higher than is generally assumed for TNOs. By way of comparison, the albedo of 1998 WW 31 for an assumed density of 1000 kg m −3 is p R =0.054 (Veillet et al 2002) and the average of 9 TNOs with radiometrically determined diameters is p R = 0.08 (Altenhoff et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…near a density of 1000 kg m −3 , the albedo is greater than 0.1, significantly higher than is generally assumed for TNOs. By way of comparison, the albedo of 1998 WW 31 for an assumed density of 1000 kg m −3 is p R =0.054 (Veillet et al 2002) and the average of 9 TNOs with radiometrically determined diameters is p R = 0.08 (Altenhoff et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…It is a red object (Santos-Sanz et al 2009), and its surface seems to be covered by some water ice (Barkume et al 2008). Observations in the millimeter range gave a first estimation of 2002 TC302 diameter to be less than 1211 km with an albedo >5.1% (Altenhoff et al 2004;Grundy et al 2005). Stansberry et al (2008) reported the detection of this body with MIPS in the two 24 and 70 μm bands with SNR < 5, and they estimated a diameter of 1150 +337 −325 km, a geometric albedo of 3.1 +2.9 −1.2 , and η = 2.3 ± 0.5.…”
Section: Resonant (84522) 2002 Tc302mentioning
confidence: 99%
“…In this technique, the measured thermal infrared flux (or fluxes) from an object is converted to a diameter using models in which the thermal emission properties and surface temperature distributions of the object are assumed (Altenhoff et al 2004;Cruikshank et al 2005). Owing to the uncertainties in the appropriate model parameters, errors in these size determinations are large.…”
Section: Introductionmentioning
confidence: 99%